Perancangan Instalasi Tenaga Listrik di Bengkel Universitas Negeri Manado - Pattinasarany, Jacki; Ridwan, Ridwan; Kilis, Billy; Rapar, Jocke (Department of Electrical Engineering Education, Faculty of Engineering, State University of Manado, 2022)
AbstractÃ¢â‚¬â€ The need for electrical energy and electrical installations is a system of electrical equipment in buildings related to each other. For the need for electrical energy and electrical installations to be carried out properly, it must meet the requirements stated in the General Electrical Installation Requirements (PUIL). One of the goals of an electrical installation system in a building is to control so that a building can function as expected. The electrical power needed and the safety and conductors are used so that the electrical installation system is safe and reliable when the building is operating. Referring to the description, the author is interested in understanding and researching further about the conductors and safety installed in the Unima workshop building. The authors obtain research data by conducting case studies where a set of data is collected, processed, compared, and analyzed. The results showed that the Unima workshop electrical resources were 27.630 W. AbstrakÃ¢â‚¬â€ Kebutuhan energi listrik dan instalasi listrik adalah sistem perlengkapan listrik pada bangunan yang berkaitan satu sama lain. Agar kebutuhan energi listrik dan instalasi listrik terselenggara dengan baik maka harus memenuhi syarat yang telah tertuang pada Persyaratan Umum Instalasi Listrik (PUIL). Salah satu tujuan dari adanya sistem instalasi listrik pada sebuah bangunan adalah mengontrol agar sebuah bangunan dapat berfungsi sebagaimana yang diharapkan. Baik daya listrik yang dibutuhkan maupun pengaman dan penghantar yang dipakai, agar pada saat bangunan tersebut beroperasi, maka sistem instalasi listriknya aman dan handal. Mengacu dari uraian tersebut, penulis tertarik untuk memahami dan meneliti lebih jauh mengenai penghantar dan pengaman yang terpasang pada bangunan bengkel Unima. Dalam melakukan evaluasi penulis memperoleh data penelitian dengan cara melakukan studi kasus dimana sekumpulan data dikumpulkan, diolah, dibandingkan, dan dianalisa. Hasil penelitian menunjukan sumber daya listrik bengkel Unima sebesar 27,630 W.